Social and Economic Importance of Modern Education System: General Overview: आधुनिक शिक्षा प्रणाली का सामाजिक एवं आर्थिक महत्त्व: सामान्य अवलोकन - Bohra, Alka; Bohra, Jai Babber (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
Since changes take place in the society and country with time, the objectives of education also change with time. For example, in the Vedic period, the teaching of Veda mantras was considered sufficient. But in the present times, emphasis is given on vocational education for human development. At present, without computer education, a person is considered almost uneducated, because the use of computers has increased in daily life. At this time, there is a need to reform the modern education system to increase productivity through education, achieve social and national integration, modernize India and develop moral, social and spiritual values. There is an abundance of traditional and theoretical curriculum in the present education system. In its place, modern and practical curriculum should be given proper place, and there is also a need to make it more employment oriented. Abstract in Hindi Language: चूँकि समाज एवं देश में समय के अनुसार परिवर्तन होते रहते हैं इसलिए शिक्षा के उद्देश्यों पर भी समय के अनुसार परिवर्तन होते हैं। उदाहरण के लिए वैदिक काल में वेदमंत्रों की शिक्षा को ही पर्याप्त मान लिया जाता था। किन्तु वर्तमान काल में मनुष्य के विकास के लिए व्यावसायिक शिक्षा पर जोर दिया जाता है। वर्तमान समय में कंप्यूटर की शिक्षा के बिना मनुष्य को लगभग ही अशिक्षित माना जाता हैं, क्योंकि दैनिक जीवन में अब कंप्यूटर का प्रयोग बढ़ा हैं। इस समय शिक्षा द्वारा उत्पादकता बढ़ाने सामाजिक एवं राष्ट्रीय एकीकरण करने, भारत का आधुनिकरण करने तथा नैतिकए सामाजिक एवं आध्यात्मिक मूल्यों का विकास करने के लिए आधुनिक शिक्षा प्रणाली में सुधार की आवश्यकता है। वर्तमान की शिक्षा प्रणाली में पारम्परिक एवं सैद्धांतिक पाठ्यक्रम की अधिकता हैं। इसके स्थान पर आधुनिक एवं प्रायोगिक पाठ्यक्रम को समुचित स्थान दिया जाना चाहिए, साथ ही इसे अधिक रोजगारोन्मुखी बनाएं जाने की भी जरूरत हैं। Keywords: वैदिक काल, आधुनिक शिक्षा प्रणाली, सामाजिक, व्यावसायिक, तकनीकी शिक्षा।